Development of an automated kinetic profiling system with online HPLC for reaction optimization. Issue 9 (2nd April 2019) - Christensen, Melodie; Adedeji, Folarin; Grosser, Shane; Zawatzky, Kerstin; Ji, Yining; Liu, Jinchu; Jurica, Jon A.; Naber, John R.; Hein, Jason E.
Abstract : Application of an automated profiling system with online HPLC uncovers an induction period in a cross-coupling and facilitates catalyst optimization. Abstract : Automated kinetic profiling is a valuable tool for providing insights into key mechanistic features of complex catalytic systems. In an attempt to optimize a palladium-catalyzed Suzuki cross-coupling reaction, automated kinetic profiling was utilized with offline liquid chromatography to monitor reaction progress. Upon uncovering analytical sample instability issues, an online HPLC capability was developed and implemented through integration of a Chemspeed liquid handling robot with an Agilent HPLC to facilitate automated reaction set-up and monitoring. Application of this capability resulted in the observation that precatalyst activation was a key factor influencing the reaction rate. Leveraging this mechanistic insight, a more efficient method to access the active catalyst was developed. This change resulted in a five-fold increase in the reaction rate.